The Citizenship Criterias for the Candidacy in Indonesian General Election: The Formality of Validation Process - Dwijayanti, Rizkya; Edwinarta, Caesar Demas (Fakultas Syariah INSURI Ponorogo, 2023)
Democracy is a system where the government should prioritize the people’s aspiration in implementing the policies because the people are a source of the power itself. A good Election system is a key of a good democracy system. This article is a research result of the citizenship validation in a government election. In fact, the citizenship validation mechanism is still not available in Indonesia as some violation cases happened during the Regent Election 2020 in Sabu Raijua. This research uses qualitative method and reference study analysist approach to deeply analyze the implementation of the citizenship validation during the general election in Indonesia. In addition, the theory of system and the concept of the democracy will be also used as an analysist so that it can give some descriptions and considerations to improve the quality of the next general election in Indonesia. The citizenship validation process also can be applied in other government administration affairs to support a better democracy implementation in the future.